Intussusception and Volvulus secondary to jejunal Adenocarcinoma in an adult Nigerian male; a case report (2010)
A 31 year-old Nigerian man with jejuno-jejunal intussusception with the lead point being an adenocarcinoma complicated by small intestinal volvulus is presented. The subtle clinical features of an underlying small bowel malignancy were masked by the overwhelming clinical and radiological features of intussusception. This rare case is reported to remind clinicians to have an increased index of suspicion of malignancy in patients who present with the usual features of chronic anemia, weight loss and loss of appetite with an intra-abdominal mass. The presentation of acute intestinal obstruction, with mesenteric vein thrombosis probably due to intussusception or volvulus should not however lower the suspicion. Histological evaluation of surgical biopsies is of immense importance.